The discovery of Stromatolites developing at 3570 m above sea level in a high-altitude volcanic lake Socompa, Argentinean Andes - Farías, María E. (2013)
We describe stromatolites forming at an altitude of 3570 m at the shore of a volcanic lake Socompa, Argentinean Andes. The water at the site of stromatolites formation is alkaline, hypersaline, rich in inorganic nutrients, very rich in arsenic, and warm (20-24°C) due to a hydrothermal input. The stromatolites do not lithify, but form broad, rounded and low-domed bioherms dominated by diatom frustules and aragonite micro-crystals agglutinated by extracellular substances. In comparison to other modern stromatolites, they harbour an atypical microbial community characterized by highly abundant representatives of Deinococcus-Thermus, Rhodobacteraceae, Desulfobacterales and Spirochaetes. Additionally, a high proportion of the sequences that could not be classified at phylum level showed less than 80% identity to the best hit in the NCBI database, suggesting the presence of novel distant lineages. The primary production in the stromatolites is generally high and likely dominated by Microcoleus sp. Through negative phototaxis, the location of these cyanobacteria in the stromatolites is controlled by UV light, which greatly influences their photosynthetic activity. Diatoms, dominated by Amphora sp., are abundant in the anoxic, sulfidic and essentially dark parts of the stromatolites. Although their origin in the stromatolites is unclear, they are possibly an important source of anaerobically degraded organic matter that induces in situ aragonite precipitation. To the best of our knowledge, this is so far the highest altitude with documented actively forming stromatolites. Their generally rich, diverse and to a large extent novel microbial community likely harbours valuable genetic and proteomic reserves, and thus deserves active protection. Furthermore, since the stromatolites flourish in an environment characterized by a multitude of extremes, including high exposure to UV radiation, they can be an excellent model system for studying microbial adaptations under conditions that, at least in part, resemble those during the early phase of life evolution on Earth.